The influence of stressful life events on procrastination among college students: multiple mediating roles of stress beliefs and core self-evaluations - Ma, Xiaole; Li, Zeheng; Lu, Furong (Frontiers in Psychology, 2023)
Few studies have documented the relationship between stressful life events and procrastination, which is a prevalent and troubling problem among college students. In this regard, the current study examined the association between stressful life events and procrastination through potential mediating effects of stress beliefs and core self-evaluations. A cross-sectional design was carried out and data were collected from a total of 794 Chinese college students with measures of stressful life events, core self-evaluations, stress beliefs, and procrastination. Results revealed that stressful life events was positively associated with procrastination in college students. Stress beliefs and core self-evaluations played multiple mediating roles in this relationship. The study provided a novel perspective of finding the possible causes of procrastination in college students and highlighted the roles of stress beliefs and core self-evaluations.